PENGARUH KUALITAS PELAYANAN BPJS, HUBUNGAN KOMUNIKASI DOKTER-PASIEN, WAKTU TUNGGU PELAYANAN RAWAT JALAN TERHADAP KEPUASAN PASIEN DI KLINIK YAI MEDIKA - Pratama, Muhammad Anis; Arifin, Samsul (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Currently, the health sector has experienced very rapid development, competition is increasingly widespread in providing services to consumers. This research was conducted with the aim of finding out the factors that influence patient satisfaction. This research used a quantitative approach with a sample of 100, and analysis was carried out using Structural Equation Modeling (SEM) with the help of the Smart-PLS version 4.0 device. This research involves outer model testing, inner model testing, mediation testing and hypothesis testing. Based on the results of the validity test, it indicates that the loading factor value > 0.7 and the AVE value > 0.5 are declared valid. The reliability test indicates that the composite reliability and Cronbach's alpha values ​​> 0.7 are said to be reliable. It can be concluded that BPJS Service Quality (X1) and Outpatient Service Waiting Time (X3) have a positive and significant effect on Patient Satisfaction (Y1). Meanwhile, the Doctor-Patient Communication Relationship (X2) has an insignificant negative effect on Patient Satisfaction (Y1). Keywords: BPJS Service Quality, Waiting Time for Outpatient Services, Doctor-Patient Communication Relationship, Patient Satisfaction